Conventioneers [videorecording (DVD)] - Stephens, Mora, 1976-; Mabe, Matthew; Koons, Woodwyn; Friedman, Alek (Cinema Libre Distribution, 2007)
A young Republican man comes to New York for the first time to be a delegate in the Republican National Convention and falls into an unlikely affair with a girl he knew in college -- a Democrat who has returned to the city to protest the convention. Conventioneers is an ironic Romeo & Juliet story set against the real 2004 RNC that explores the consequences of the divide in American politics.